Osteogenic Potential of the Transcription Factor c-MYB - Oralova, V; Matalova, E; Killinger, M; Knopfova, L; Smarda, J; Buchtova, M (Calcified tissue international, 2017)
The transcription factor c-MYB is a well-known marker of undifferentiated cells such as haematopoietic cell precursors, but recently it has also been observed in differentiated cells that produce hard tissues. Our previous findings showed the presence of c-MYB in intramembranous bones and its involvement in the chondrogenic steps of endochondral ossification, where the up-regulation of early chondrogenic markers after c-myb overexpression was observed. Since we previously detected c-MYB in osteoblasts, we aimed to analyse the localisation of c-MYB during later stages of endochondral bone formation and address its function during bone matrix production. c-MYB-positive cells were found in the chondro-osseous junction zone in osteoblasts of trabecular bone as well as deeper in the zone of ossification in cells of spongy bone. To experimentally evaluate the osteogenic potential of c-MYB during endochondral bone formation, micromasses derived from embryonic mouse limb buds were established. Nuclear c-MYB protein expression was observed in long-term micromasses, especially in the areas around nodules. c-myb overexpression induced the expression of osteogenic-related genes such as Bmp2, Comp, Csf2 and Itgb1. Moreover, alizarin red staining and osteocalcin labelling promoted mineralised matrix production in c-myb-overexpressing cultures, whereas downregulation of c-myb by siRNA reduced mineralised matrix production. In conclusion, c-Myb plays a role in the osteogenesis of long bones by inducing osteogenic genes and causing the enhancement of mineral matrix production. This action of the transcription factor c-Myb might be of interest in the future for the establishment of novel approaches to tissue regeneration.
Keywords: Mineralised matrix; osteokalcin; Proto-Oncogene Proteins c-myb; kosti a kostní tkáň; Up-Regulation; osteogeneze; osteoblasty; buněčná diferenciace; Osteoblasts; upregulace; chondrogeneze; Micromass cultures; Mouse limbs; Animals; protoonkogenní proteiny c-myb; PCR Array; Chondrogenesis; zvířata; myši; Osteocalcin; Osteogenesis; Mice; Bone and Bones; Cell Differentiation